2022
DOI: 10.1093/jn/nxab392
|View full text |Cite
|
Sign up to set email alerts
|

A Specifically Tailored Multistrain Probiotic and Micronutrient Mixture Affects Nonalcoholic Fatty Liver Disease—Related Markers in Patients with Obesity after Mini Gastric Bypass Surgery

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is frequent among patients undergoing bariatric surgery. Beyond weight reduction, dietary supplements like micronutrients or probiotics that modify insulin resistance and lipotoxicity can be used to prevent or delay the progression of liver disease. Objectives We evaluated the effect of a dietary approach with a specifically tailored multistrain probiotic and micronutrient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 70 publications
0
21
0
1
Order By: Relevance
“…These studies included 741 individuals (392 patients with NAFLD, and 349 healthy individuals). The included studies were published from Jan 2020 to Jul 2022, and conducted in Asia ( 9 , 28 ), North America ( 11 ), and Europe ( 8 , 10 , 12 , 15 , 16 , 18 , 29 , 30 ), respectively. There are eight studies with the probiotics intervention, two with synbiotics intervention, and one with prebiotics intervention for patients with NAFLD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies included 741 individuals (392 patients with NAFLD, and 349 healthy individuals). The included studies were published from Jan 2020 to Jul 2022, and conducted in Asia ( 9 , 28 ), North America ( 11 ), and Europe ( 8 , 10 , 12 , 15 , 16 , 18 , 29 , 30 ), respectively. There are eight studies with the probiotics intervention, two with synbiotics intervention, and one with prebiotics intervention for patients with NAFLD.…”
Section: Resultsmentioning
confidence: 99%
“…Although multiple treatments have been used to improve or prevent NAFLD disease, a healthy lifestyle is always the most common and effective intervention for NAFLD. For example, a body mass loss of 3–5% could decrease cardiovascular risk, a body mass loss of 2–5% lower the level of HbA1c in T2DM patients, and a body mass loss of 7–10% could improve insulin sensitivity, liver enzyme concentrations, and liver steatosis and fibrosis in obese NAFLD patients ( 10 , 31 ). Researchers investigated the BMI, and dietary habits (energy, carbohydrate, and fat intake) of NAFLD patients in the included trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…levels of ALT, AST, TC, HDL, and TNF-α and improve IR in patients with NASH (86). In addition, a randomized controlled study revealed that patients with NAFLD treated daily with Lactobacillus and Bifidobacterium species showed decreased levels of ALT and γGT, decreased counts of CD4+ T-cells and CD8+ T-cells, and improved HS fibrosis (87).…”
Section: Craven Et Al (1)mentioning
confidence: 99%
“…Previous investigations have suggested that probiotics enhance the barrier function of epithelial cells and decrease intestinal permeability and endotoxemia in patients with liver disease. Probiotic therapy can significantly decrease the levels of ALT, AST, TC, HDL, and TNF-α and improve IR in patients with NASH ( 86 ). In addition, a randomized controlled study revealed that patients with NAFLD treated daily with Lactobacillus and Bifidobacterium species showed decreased levels of ALT and γGT, decreased counts of CD4+ T-cells and CD8+ T-cells, and improved HS fibrosis ( 87 ).…”
Section: Microbiota and Mitochondria: Potential Therapeutic Strategie...mentioning
confidence: 99%